Compliance with national guidelines for stroke in radiology. (September 2015) - Komenda, Izabela; Knight, Vincent; Williams, Hannah Mary
Abstract: Stroke is a medical emergency, and if patient outcomes are to be optimised there should be no delays in accessing treatment. This project focuses on the application of Operational Research methodology to investigate how a hospital can comply with the revised computerised tomography (CT) scanning guidelines for stroke. Such guidelines, released by the Royal College of Physicians recommend a 50% reduction in time from hospital admission to report of a CT head scan to just 12 hours. The results of statistical analyses of historical data were used to populate a discrete event simulation model of patient flow through the CT scanning unit. The model was then used to explore a number of operational modifications to the CT scanning system through a series of scenario analyses. The results of this investigation presented evidence of a number of strategies to support operational improvements in relation to revised stroke guidelines.